The (Fiscal) Usurpation of Indigenous Territories in Costa Rica, 1977–2024 (Part I): Traces of a State in Debt (Revista Rupturas, 2026)
In Costa Rica, the usurpation of lands from Indigenous peoples by social actors external to their territories is a historical problem. This article examines the trend records of Indigenous territories in primary institutional sources and secondary source documentation to understand the period between 1977 and 2024, when Indigenous Law No. 6172 was in force. However, this usurpation is also problematized as embezzlement from a fiscal perspective that has not been studied as tax plundering of the national economy. This article, PART I, discusses the actions of land return by a State that remains in debt, from the construction of the theoretical problem, legislation, and documentation.
Keywords: Indigenous autonomy; territorial struggle; tax usurpation; ndigenous peoples; land return